Gender Inclusive Education in Preventing Sexual Violence in Islamic Boarding Schools - Intan Verly Syafitri; Firman; Dina Sukma (Aslim: Journal of Education and Islamic Studies, 2025)
Islamic boarding schools, as educational institutions that have an important role in forming the character and morals of students, are required to adopt a fair approach. This is important considering that sexual violence often stems from entrenched gender injustice and inequality. The aim of this article is to answer two central questions: Why does sexual violence occur in Islamic boarding schools? How is sexual violence prevented in Islamic boarding schools? The data collection process includes four stages, starting with the inclusion stage and the exclusion stage. This data was collected through the Google Scholar search engine using the keywords "sexual violence in Islamic boarding schools" and "Inclusive and gender equal education in Islamic boarding schools". The root of the problem of sexual violence in Islamic boarding schools lies in the hierarchical relationship between kiai and santri, the maintenance of patriarchal culture, and the absolute obedience of santri to kiai. These three factors also cause the majority of incidents of sexual violence in Islamic boarding schools to go unreported due to fear among the victims and their families. To overcome this, gender inclusive education is needed which is reflected in the Gender Equality Curriculum (KKG). This curriculum establishes a gender-responsive way of thinking and acting based on gender justice and equality in all elements of the education system. Gender inclusive education also creates a gender neutral learning system.